Jarimah Qadzaf and Uqubatnya, Comparison Between Qonun No. 4 of 2014 concerning Jinayat and the Criminal Code - Saifuddin AW; Mhd Yadi Harahap (Jurnal Cendikia ISNU SU, 2025)
The phenomenon of accusations of adultery without real evidence and defamation raises serious problems in the moral, social, and legal order of society. In the perspective of Islamic law, this act is known as jarimah qadzaf, which not only damages the reputation of the individual but also interferes with social integrity and the principle of justice. The application of qadzaf in Indonesia shows that there is a fundamental difference between national law and the sharia qanun that applies in Aceh, thus creating challenges in legal harmonization. This study aims to analyze the concept of jarimah qadzaf and its uqubat, as well as compare its application between Qanun Aceh No. 4 of 2014 concerning Jinayat and the Criminal Code (KUHP). The research method used is normative research with a comparative law approach, based on the study of legal documents in the form of the Qur'an, Hadith, Qanun, and the Criminal Code, as well as relevant secondary legal literature. The analysis is carried out qualitatively to understand the substantive, philosophical, and procedural aspects of the existing regulations. The results of the study showed that Qanun Aceh placed qadzaf as a hudud crime with the sanction of eighty lashes, focusing on the protection of individual honor and preventive effects. While the Criminal Code places the accusation of adultery as a defamation complaint with imprisonment or fines, it emphasizes procedural certainty rather than moral and spiritual aspects. This difference reflects the different legal philosophies between the sharia approach and national positive law, but both have the goals of protecting the community and enforcing justice. In conclusion, a deep understanding of qadzaf and its comparison with the Criminal Code is important to integrate moral principles, ethics, and legal procedures, as well as ensure fair protection of individuals and social interests.